The Crucible of war, 1939-1945 - Greenhous, Brereton, 1929- (Official history of the Royal Canadian Air Force, 1994)
Some 40 per cent of RCAF aircrew who served overseas during the Second World War did so in RACF squadrons. This is their story. The first RCAF squadron to see action in the Second World War was No. 1 Fighter Squadron, later to be No. 401, which from 18 August 1940 participated in the Battle of Britain. The last, in a still active theatre, were Nos. 435 and 436, delivering supplies in Burma until late August 1945. In between, RCAF squadrons served in all the major commands and in most major theatres of war. They were engaged by day and by night in air-to-air combat, strategic bombing, photo-reconnaissance, anti-shipping strikes and anti-submarine patrols, close air support, interdiction, and tactical airlift supply. The Crucible of War is divided into five parts: Air Policy, the Fighter War, the Maritime Air War, the Bomber Air War, and the Air Transport War. The authors break new ground by demonstrating the influence of senior RCAF officers in shaping the execution of Canadian air policy, and they show how senior RCAF officer were permitted to determine the pace of Canadianization of the RCAF. Many operations are described in detail from a wide variety of documentary sources, among them the unsuccessful battle of attrition that resulted from Fighter Command's offensive over France in 1941-42, and the actions of the RCAF's No 83 Group in Second Tactical Air Force, which provided air support for the British Second Army. Overdue notice is accorded the anti-shipping strike squadrons of Coastal Command. No 6 Group's battle with German night-fighters is recounted within the framework of complex electronic measures and counter-measures developed by both sides. The RCAF, with a total strength of 4061 officers and men on 1 September 1939, grew by the end of the war to a strength of more than 263,000 men and women. This important and well-illustrated new history shows how they contributed to the resolution of the most significant conflict of our time.